Assessing the role of religiosity on the behavioral intention to buy islamic insurance / Shah Rizal Zambahari … [et al.] - Zambahari, Shah Rizal; Zainuddin, Anizah; Ariffin, Shahirah; Abd Manan, Hasman (Research Management Institute (RMI), 2013)
Insurance industry in Malaysia has experience tremendous growth since its inception during colonial period between the 18th and 19th centuries. Market penetration of life insurance, as measured in terms of the total number of policies in force to total population, grew to 39.3% as at end-June (end-June 2006: 38.7%) (The Star, September 8, 2007). But less than 7% of Malaysians are covered by family takaful plans in 2006 although 52 percent of the Malaysian population constitutes Muslim. This research was conducted to identify the level of awareness among Malays toward the importance of life insurance